Tetrahedron beam imaging with a multi‐pixel thermionic emission X‐ray source and a photon‐counting detector: A benchtop experimental study. Issue 11 (16th September 2021) - Chen, Qinghao; Zhou, Shuang; Tan, Yuewen; Hao, Yao; Zhang, Zhongwei; Mazur, Tom; Zhang, Tiezhi
Abstract: Purpose: A tetrahedron beam (TB) X‐ray system with a linear X‐ray source array and a linear detector array positioned orthogonal to each other may overcome the X‐ray scattering problem of traditional cone‐beam X‐ray systems. We developed a TB imaging benchtop system using a linear array X‐ray source to demonstrate the principle and benefits of TB imaging. Methods: A multi‐pixel thermionic emission X‐ray (MPTEX) source with 48 focal spots in 4‐mm spacing was developed in‐house. The X‐ray beams are collimated to a stack of fan beams that are converged to a 6‐mm wide multi‐row photon‐counting detector (PCD). The data collected with a sequential scan of the sources at a fixed view angle were synthesized to a 2D radiography image by a shift‐and‐add algorithm. The data collected with a full rotation of the system were reconstructed into 3D TB CT (TBCT) images using an Feldkamp, Davis, and Kress (FDK)‐based computed tomography (CT) algorithm modified for the TB geometry. Results: With an 18.8‐cm long source array and a 35‐cm long detector array, the TB benchtop system provides a 25‐cm cross‐sectional and 8‐cm axial field of view (FOV). The scatter‐to‐primary ratio (SPR) was approximately 17% for TB, as compared with 120% for cone beam geometry. The TBCT system enables reconstructions in two‐dimensional radiography and three‐dimensional volumetric CT. The TBCT images were free of "cupping" artifacts and have similar image quality as diagnostic helical CT. Conclusions: A TB imaging benchtop imaging system was successfully developed with MPTEX source and PCD. Phantom and animal cadaver imaging demonstrated that the TB system can produce satisfactory radiographic X‐ray images and 3D CT images with image quality comparable to diagnostic helical CTs.